Solubilization of active opiate receptors. - Simonds, W F (1980)
Receptors that reversibly bind opiates and opioid peptides have been solubilized from brain and neuroblastoma-glioma hybrid cell NG108-15 membranes. Active receptors are specifically solubilized with a new type of detergent 3-[(3-cholamidopropyl)dimethylammonio]-1-propanesulfonate, which is a zwitterionic derivative of cholic acid. The solubilized receptor complexes behave as large molecules with a Stokes radius of 70 A and contain protein as an essential constituent.